E Edukasi Pertolongan Pertama Pada Kecelakaan (P3K) Bagi Palang Merah Remaja (PMR) Meningkatkan Kesiapan Menolong Korban Kecelakaan - Lusmiati Anisah, Retno; Parmilah, Parmilah (STIKES Ngesti Waluyo, 2020)
Abstract Accidents can happen anywhere and anytime, especially at school. There is a grace period that must be filled by a trained first aid until the victim is helped by medical personnel. First Aid for Accidents (P3K) at school, often provided by members of the Youth Red Cross (PMR). PMR's knowledge and attitude will affect the speed and accuracy in helping victims. Complications or disabilities due to accidents at school can be prevented if first aid is provided quickly and precisely. Several studies have found that the behavior of helping accident victims among students tends to be low, as is the case for PMR Wira members. The purpose of this scientific article is to determine the effect of education about first aid on the readiness to help PMR Wira members. This scientific paper uses a one group pre test post test design research design. The sample technique used was purposive sampling method of 32 respondents. Collecting data using a valid and reliable help readiness questionnaire. Data analysis using the Wilcoxon test. Readiness to help before being given education was at a sufficient level and less, respectively, as many as 16 students (50%), and as many as 32 students (100.0%) were at a good level after being given education about first aid. There is a significant difference in the level of readiness to help PMR Wira members before and after being given intervention (p = 0.000